Controlling the critical parameters of ultrasonication to affect the dispersion state, isolation, and chiral nematic assembly of cellulose nanocrystals - Robertus Wahyu N. Nugroho; Blaise L. Tardy; Sayed M. Eldin; R.A. Ilyas; Melbi Mahardika; Nanang Masruchin (Ultrasonics Sonochemistry, 2023)
Cellulose nanocrystals (CNCs) are typically extracted from plants and present a range of opto-mechanical properties that warrant their use for the fabrication of sustainable materials. While their commercialization is ongoing, their sustainable extraction at large scale is still being optimized. Ultrasonication is a well-established and routinely used technology for (re-) dispersing and/or isolating plant-based CNCs without the need for additional reagents or chemical processes. Several critical ultrasonication parameters, such as time, amplitude, and energy input, play dominant roles in reducing the particle size and altering the morphology of CNCs. Interestingly, this technology can be coupled with other methods to generate moderate and high yields of CNCs. Besides, the ultrasonics treatment also has a significant impact on the dispersion state and the surface chemistry of CNCs. Accordingly, their ability to self-assemble into liquid crystals and subsequent superstructures can, for example, imbue materials with finely tuned structural colors. This article gives an overview of the primary functions arising from the ultrasonication parameters for stabilizing CNCs, producing CNCs in combination with other promising methods, and highlighting examples where the design of photonic materials using nanocrystal-based celluloses is substantially impacted.